1994
DOI: 10.1111/j.1439-0507.1994.tb00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological analysis of Candida yeasts by pulsed‐field gel electrophoresis

Abstract: The purpose of this study was to determine whether yeast isolates from mothers and their new-borns are of the same genotype. In this investigation, 103 parturient mothers and their children were examined for colonization by yeasts by sampling the vaginal secretions at delivery and by taking swabs from the oral mucosa and the anus of the children on the third day after parturition. The samples were cultured on Sabouraud glucoseagar and incubated for 48 h at 37 degrees C. Differentiation of the isolates was achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…These data correlate with findings in adult persons with advanced HIV infection [2]. Colonization with Candida species in HIV‐negative women and their newborns was found at a much lower rate (37.9 to 63%, 15.4 to 33%, respectively) [7, 8]. However, the DNA‐fingerprinting methods revealed more differences among yeast isolates between individuals of a mother/child pair, than the phenotypic appearance of the cultured yeasts may suggest.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These data correlate with findings in adult persons with advanced HIV infection [2]. Colonization with Candida species in HIV‐negative women and their newborns was found at a much lower rate (37.9 to 63%, 15.4 to 33%, respectively) [7, 8]. However, the DNA‐fingerprinting methods revealed more differences among yeast isolates between individuals of a mother/child pair, than the phenotypic appearance of the cultured yeasts may suggest.…”
Section: Discussionsupporting
confidence: 78%
“…Recent studies using molecular typing techniques have indicated, that an individual patient is usually colonized by a single Candida strain that may later cause the occurrence of OPC [4], but the exact mechanisms of how a colonizing strain causes recurrent OPC are still unclear [5]. At present, some epidemiologic data concerning the transmission of Candida isolates from parents to their children suffering from leukaemia as well as from mothers to their newborns are available, but studies in HIV‐infected mothers and their children have not been carried out so far [6–8]. Among other DNA typing assays, Southern blot hybridization with the use of an appropriate Candida albicans specific probe was considered by several authors as a reference method for the detection of genetic diversity among clinical isolates of C. albicans from AIDS patients [4, 9–12].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, a variety of molecular techniques have emerged which allow a high degree of reliability in epidemiologic tracking of various strains of pathogenic yeasts. These techniques include pulsed field gel electrophoresis [4][5][6] , restriction fragment length polymorphism (RFLP) [6][7][8][9] , Southern hybridization of specific probes 10,11 , RAPD [11][12][13][14][15][16][17][18][19] , and combinations of various methods.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular typing techniques have indicated that one-third of premature infants were colonized and that mother-to-infant transmission of the identical strain occurred in 14% of infants 24 . In another study, there were six cases among 103 newly parturient women in which both mother and infant were colonized by identical strains of C. albicans 5 . C. albicans and other related yeast are frequently commensal flora on mucosal sites, and it is possible for individuals to carry more than one strain of yeast at a time 25 .…”
Section: Discussionmentioning
confidence: 99%
“…These techniques include pulsed field gel electrophoresis [4][5][6] , restriction fragment length polymorphism (RFLP) [6][7][8][9] , Southern hybridization of specific probes 10,11 , RAPD [11][12][13][14][15][16][17][18][19] , and combinations of various methods. Recently, Soll published an extensive review of the methods and pitfalls associated with DNA fingerprinting of fungal organisms 1 .…”
Section: Discussionmentioning
confidence: 99%